2015
DOI: 10.1016/j.cj.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Divergence in homoeolog expression of the grain length-associated gene GASR7 during wheat allohexaploidization

Abstract: Hexaploid wheat has triplicated homoeologs for most of the genes that are located in subgenomes A, B, and D. GASR7, a member of the Snakin/GASA gene family, has been associated with grain length development in wheat. However, little is known about divergence of its homoeolog expression in wheat polyploids. We studied the expression patterns of the GASR7 homoeologs in immature seeds in a synthetic hexaploid wheat line whose kernels are slender like those of its maternal parent (Triticum turgidum, AABB, PI 94655… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
8
0
2
Order By: Relevance
“…Many of the methylation differences in the duplicate soybean genes can be attributed to transposon insertions that are present in one member of the pair Kim et al, 2015). These studies along with data from specific wheat (Triticum aestivum) loci (Shitsukawa et al, 2007;Hu et al, 2013;Zhang et al, 2015) and maize (West et al, 2014) suggest that DNA methylation does not play a major global role in differentiating subgenomes, but it can contribute to locus-specific divergence of retained duplicates.…”
Section: Chromatin-based Long-term Contributions To Regulatory Diversmentioning
confidence: 77%
“…Many of the methylation differences in the duplicate soybean genes can be attributed to transposon insertions that are present in one member of the pair Kim et al, 2015). These studies along with data from specific wheat (Triticum aestivum) loci (Shitsukawa et al, 2007;Hu et al, 2013;Zhang et al, 2015) and maize (West et al, 2014) suggest that DNA methylation does not play a major global role in differentiating subgenomes, but it can contribute to locus-specific divergence of retained duplicates.…”
Section: Chromatin-based Long-term Contributions To Regulatory Diversmentioning
confidence: 77%
“…Because VTE4 catalyses the conversion of γ and δ forms of both T and T3 into α and β forms, the elevated levels of VTE4_1 transcripts are consistent with the relative abundance of the forms of vitamin E in oat seeds: α‐T3 > αT > βT3 > βT (Gutierrez‐Gonzalez et al ., ). Unequal contributions from homeologs in polyploids have been previously shown in wheat (Akhunova et al ., ; Zhang et al ., ), cotton (Adams et al ., ) and rapeseed (Xu et al ., ) and are commonly due to mutations in regulatory regions or epigenetic changes in both methylation patterns and histone modifications. In addition to VTE4_1, the other enzyme with homeologs exhibiting a high correlation ( r = 0.97–1) with T, T3 and total vitamin E forms is HPPD.…”
Section: Discussionmentioning
confidence: 99%
“…10 gene had functions that affect the TGW, PH and SL during the maturity stage. To date, some grain weight genes have been isolated, such as Ppd-D1 [56], CKX6-D1 [57], GS1a [11], GW2 [8, 5859], GS-D1 [60], Sus [9, 61], GASR7 [6263], TEF-7 [64], CWI [65], and 1-FEH-w3 [6667]. Using sequence comparison and the analysis of protein domains with PROSITE (http://prosite.expasy.org/), we found that TaSnRK2 .…”
Section: Discussionmentioning
confidence: 99%